2013
DOI: 10.1007/s00586-013-2755-z
|View full text |Cite
|
Sign up to set email alerts
|

The results of closing wedge osteotomy with posterior instrumented fusion for the surgical treatment of congenital kyphosis

Abstract: Purpose There exist not much data regarding the surgical treatment of pure congenital kyphosis (CK) in the literature. The purpose of this study was to evaluate the results of closing wedge osteotomy with posterior instrumented fusion in patients with congenital kyphotic deformity. Methods We retrospectively evaluated the radiographical results of 10 patients who were subject to closing wedge vertebral osteotomy and posterior instrumented fusion due to CK. The mean age of the patients at surgery was 12.6 ± 3.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 26 publications
(31 reference statements)
0
27
0
2
Order By: Relevance
“…Congenital kyphosis is caused by a mismatch during the final stages of ossification and cartilage formation in embryological development. Ongoing growth in the posterior elements of the spine when there is a formation and/or segmentation failure in anterior structures of the spinal column may cause progressive segmental sharp kyphosis [12]. Other mechanisms, such as severe vertebral body and disc destruction in spinal tuberculosis can cause local, severe kyphotic deformity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Congenital kyphosis is caused by a mismatch during the final stages of ossification and cartilage formation in embryological development. Ongoing growth in the posterior elements of the spine when there is a formation and/or segmentation failure in anterior structures of the spinal column may cause progressive segmental sharp kyphosis [12]. Other mechanisms, such as severe vertebral body and disc destruction in spinal tuberculosis can cause local, severe kyphotic deformity.…”
Section: Discussionmentioning
confidence: 99%
“…The literature indicates the development of paraplegia in advanced (late-stage) post-tuberculosis kyphotic deformity because of spinal cord compression [3456]. Paraplegia or paraparesis is uncommon in spinal deformities with underlying neurofibromatosis; however, SAK that accompanies existing spinal deformity may result in worsening of neurological deficits by either a compression or stretching effect on the spinal cord [7812]. Winter et al [9] have reported six paraparesis cases with normal history within 33 cases of SAK with underlying neurofibromatosis (range, 80°–180°) [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-surgical interventions are not effective in decreasing the progression of kyphotic deformities [4]. Surgical intervention in early life is thought to be a cornerstone for these patients, because this will prevent deterioration of neurologic deficits and reduce the need for surgeries in late life when the spine becomes stiffer [1,5,6]. The wedged vertebra is mostly trapped in the thoracolumbar junction, difficult to access, with complex pathologic anatomy, closely related to the spinal cord, and in an area with abundant vascularity.…”
Section: Introductionmentioning
confidence: 99%